1992
DOI: 10.1063/1.350453
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ag doping on superconducting properties of the Bi-Pb-Sr-Ca-Cu-O tape fabricated by an Ag sheath

Abstract: The powder-in-tube method using an Ag sheath is applied to achieve high current capacity in the tapes of Bi-Pb-Sr-Ca-Cu-O (BPSCCO) with the high-Tc phase (Tc=110 K), by a combination process of cold working and sintering. Two kinds of the BPSCCO powder with and without Ag doping are used as the materials for tape fabrication. The morphology, structure, and critical current density Jc are investigated on the tapes by x-ray diffraction, differential thermal analysis, scanning electron microscope, magnetic suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because the optimum sintering temperature is very close to the partial melting temperature of the Bi-2223 phase, the slight decrease of the binding energy of the ceramic at the interface causes partial melting of the ceramic at the silver-ceramic interface. Differential thermal analysis measurements have confirmed this assumption, showing that the presence of silver lowers the partial melting point and also the melting point of Bi-2223 ceramic [4]. During the ceramic partial melting, enhancement of grain coarsening occurs and the grain boundaries characterized by the highest energy disappear.…”
Section: Surface Diffusion Coefficientmentioning
confidence: 69%
“…Because the optimum sintering temperature is very close to the partial melting temperature of the Bi-2223 phase, the slight decrease of the binding energy of the ceramic at the interface causes partial melting of the ceramic at the silver-ceramic interface. Differential thermal analysis measurements have confirmed this assumption, showing that the presence of silver lowers the partial melting point and also the melting point of Bi-2223 ceramic [4]. During the ceramic partial melting, enhancement of grain coarsening occurs and the grain boundaries characterized by the highest energy disappear.…”
Section: Surface Diffusion Coefficientmentioning
confidence: 69%
“…In the silver sheathed tapes the Bi-2223 phase forms preferentially at the interface between the silver sheath and the oxide core, because the silver reduces the melting temperature of the oxide. Thus the microstructure near the interface is different from that at the centre of the oxide core [7] and the variations of the tapes thickness and/or width result in different superconducting phase homogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these facts it is reasonable to suppose that silver added to the core would improve the critical current density of Bi2223-Ag tapes, because it would provide an additional 'interface'. The effect of silver additions in Bi2223 tapes has been investigated in several studies [2,[4][5][6][7][8]. The results were somewhat contradictory, but it was generally found that the addition does not significantly improve the properties of the tapes.…”
Section: Introductionmentioning
confidence: 99%